Design Get up Application E-Commerce Based Web Using the Agile Kanban Method ( Case Study at Bandung Digital Marketing Friends ) - Hermawan, Irman; Indriani, Indriani (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
Study This gives a clear view of How a company can face problem displacement sales from marketplaces to e-commerce websites, companies realize that depending on the marketplace it has a number of limitations and challenges.From the problems mentioned above, then _ proposed For building purposeful web application For design and develop web-based e-commerce application. In this process, System web applications use modeling Draw Io system, with PHP programming language, and phpMyAdmin database, PHP Framework Laravel 9.Test results on the system This shows that from the results Index percentage earned on each _ statement pointed out average results the percentage is 74.66% With results, then it is stated in testing to achievement utility application stated worthy accepted with Satisfactory status